A Narrative Inquiry into Indonesian Elementary Students’ Experiences in English Online Learning during Covid-19 - Ning Setio Wati; Ahmad Madkur (Jurusan PGMI FTIK IAIN Metro Lampung, 2021)
Abstract Despite the extensive research on the issues of online learning in various contexts and at any education level, there is a paucity of exploration on elementary students’ perceptions and experiences in online English learning. This study therefore attempts to fill this gap by drawing on narrative inquiry to allow students to voice and express what they perceive of learning English in online mode. Through shared reflection, the students offer a snapshot of their lived experiences related to English online learning. The findings from this narrative investigation show that the problems faced by elementary school students when English learning online by using digital media are related to individual factors, and differences in students’ family backgrounds to be actively involved in verbal communication. To overcome these challenges, the participants applied direct communication with their classmates in outside of the online class. Face-to-face language learning has a very important influence on the understanding of communication for young learners. In addition, this study suggests the importance of digital literacy for students particularly in time of online learning era. Keywords: Covid-19, elementary students, English online learning, digital media, narrative inquiry Abstrak Meskipun sudah banyak penelitian tentang pembelajaran online dalam berbagai konteks dan tingkat pendidikan, persepsi dan pengalaman siswa sekolah dasar dalam pembelajaran bahasa Inggris online masih belum banyak diteliti. Oleh karena itu penelitian ini mencoba untuk mengisi kesenjangan ini dengan melakukan penelitian inkuiri naratif yang memungkinkan siswa untuk menyuarakan dan mengekspresikan apa yang mereka rasakan dari belajar bahasa Inggris dalam mode online. Melalui refleksi bersama, para siswa menawarkan gambaran tentang pengalaman hidup mereka terkait dengan pembelajaran online bahasa Inggris. Temuan dari investigasi naratif ini menunjukkan bahwa masalah yang dihadapi siswa sekolah dasar ketika belajar bahasa Inggris online dengan menggunakan media digital adalah faktor individu dan perbedaan latar belakang keluarga siswa untuk terlibat aktif dalam komunikasi verbal. Untuk mengatasi tantangan tersebut, siswa menerapkan komunikasi langsung dengan teman sekelasnya di luar kelas online. Pembelajaran bahasa tatap muka memiliki pengaruh yang sangat penting terhadap pemahaman komunikasi bagi pelajar muda. Selain itu, penelitian ini menyarankan pentingnya literasi digital bagi siswa khususnya di era pembelajaran online. Kata kunci: Covid-19, siswa SD, pembelajaran online bahasa Inggris, media digital, narrative inquiry